2017
DOI: 10.1039/c6cp07992j
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a solid solution between [N(C2H5)4][BF4] and [N(C2H5)4][PF6] in crystal and plastic crystal phases

Abstract: The phase behavior of [N][BF] and [N][PF] (N = tetraethylammonium cation) binary systems has been investigated in the present study. Differential scanning calorimetry revealed that the crystal-to-plastic-crystal transition temperature decreases upon mixing the two salts, with a minimum at x([N][PF]) = 0.4, where x([N][PF]) denotes the molar fraction of [N][PF]. Powder X-ray diffraction analysis indicated the formation of a solid solution with a rock-salt type structure in the plastic crystal phase at all ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…228, 235, 412 and 423 K). 23,25–27 The sharp and intense endothermic peak at 423 K is associated with a high entropy value (Δ S = 22.16 J K −1 mol −1 ) which is comparable to entropy values measured during solid-plastic transition of crystals such as [(CH 3 ) 4 N]FeCl 4 (Δ S = 13.5 J K −1 mol −1 ), 24 , [(CH 3 ) 4 N]FeBrCl 3 (Δ S = 15.6 J K −1 mol −1 ), 21 , [(C 2 H 5 ) 4 N]BF 4 (Δ S = 22.0 J K −1 mol −1 ) 41 and (C 2 H 4 N 3 )(C 4 F 9 SO 3 ) (Δ S = 26.0 J K −1 mol −1 ). 42 The endothermic peak at T t = 412 K, slightly less intense than the peak at 423 K, was only observed upon the second heating run, that is to say after dehydrating the sample.…”
Section: Resultsmentioning
confidence: 99%
“…228, 235, 412 and 423 K). 23,25–27 The sharp and intense endothermic peak at 423 K is associated with a high entropy value (Δ S = 22.16 J K −1 mol −1 ) which is comparable to entropy values measured during solid-plastic transition of crystals such as [(CH 3 ) 4 N]FeCl 4 (Δ S = 13.5 J K −1 mol −1 ), 24 , [(CH 3 ) 4 N]FeBrCl 3 (Δ S = 15.6 J K −1 mol −1 ), 21 , [(C 2 H 5 ) 4 N]BF 4 (Δ S = 22.0 J K −1 mol −1 ) 41 and (C 2 H 4 N 3 )(C 4 F 9 SO 3 ) (Δ S = 26.0 J K −1 mol −1 ). 42 The endothermic peak at T t = 412 K, slightly less intense than the peak at 423 K, was only observed upon the second heating run, that is to say after dehydrating the sample.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows 6 ] binary system, the successive cooling and the second heating scans were not reproducible due to the slow kinetics for the phase transition during cooling process. 24 It also occurred in the [N 2222 4 ]) = 0.1-0.9 slightly decrease compared to the ones of the pure compounds, which results from the formation of solid solutions (see the section of XRD for details). Although a small but detectable endothermic peak, which could be due to a minor structural change, is observed around 410 K, this was not reproducible and omitted from the following discussion.…”
Section: ¹1mentioning
confidence: 98%
“…5,19,20 Addition of an inorganic salt to OIPCs has been mainly carried out to introduce mobile ions such as Li + to achieve good ion conduction, whereas mixing two OIPCs is also considered as a method to obtain high ionic conductivity, which typically focuses on the change of their structural and thermal properties. 24 Alkylammonium salts have been attracting attention in structural studies because they exhibit a variety of structural changes during thermal transitions and their highest temperature solid phase is often characterized as IPC phase. [25][26][27] Our previous study on plastic crystal phases of tetraalkylammonium salts of BF 4 ¹ and PF 6 ¹ showed that the size of the ions affects the structural type of their plastic crystal phases, which follows the radius ratio rule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is somehow unexpected and sharply contrasts with other reported similar systems forming solid solutions and exhibiting a regular trend of the transition temperature as a function of the composition. [43][44][45] To investigate the unexpected behavior of [QH]IJPF 6 ) x -IJBF 4 ) 1−x , VT powder XRD experiments were carried out up to the instrumental limit of 123 K. Still, also in this case, no changes in the diffraction patterns were detected on decreasing the temperature (Fig. S13 †).…”
Section: Solid Solutions Between [Qh]pf 6 and [Qh]bfmentioning
confidence: 99%